Unified Abstract Mechanism to Model Language Learning Activities - Sebastián, Gabriel; Tesoriero, Ricardo; Gallud, Jose A. (Computing and Informatics, 2021)
Language learning applications define exercises that are pedagogical tools to introduce new language concepts. The development of this type of applications is complex due to the diversity of language learning methodologies, the variety of execution environments and the number of different technologies that can be used. This article proposes a conceptual model to develop the activities of language learning applications. It defines a new abstraction mechanism to model these activities as part of a model-driven approach to develop applications supporting different language learning processes running on different hardware and software platforms. We define a metamodel that describes the entities and relationships representing language learning activities as well as a series of examples that use the proposed abstraction mechanism to represent different language learning activities. The modelling process is simplified using a common representation that does not affect neither the visual presentation, nor the interaction of each activity. The article includes an evaluation that analyses the product correctness, robustness, extensibility, and reusability of the obtained code. These results conclude that the code generated using the proposed approach overcomes the code generated following a traditional approach.